Older adult falls prevention behaviors 60 days post-discharge from an urban emergency department after treatment for a fall - Kalpana Narayan Shankar; Nicole J. Treadway; Alyssa A. Taylor; Alan H. Breaud; Elizabeth W. Peterson; Jonathan Howland (BMC, 2017)
Abstract Background Falls are a common and debilitating health problem for older adults. Older adults are often treated and discharged home by emergency department (ED)-based providers with the hope they will receive falls prevention resources and referrals from their primary care provider. This descriptive study investigated falls prevention activities, including interactions with primary care providers, among community-dwelling older adults who were discharged home after presenting to an ED with a fall-related injury. Methods We enrolled English speaking patients, aged ≥ 65 years, who presented to the ED of an urban level one trauma center with a fall or fall related injury and discharged home. During subjects' initial visits to the ED, we screened and enrolled patients, gathered patient demographics and provided them with a flyer for a Matter of Balance course. Sixty-days post enrollment, we conducted a phone follow-up interview to collect information on post-fall behaviors including information regarding the efforts to engage family and the primary care provider, enroll in a falls prevention program, assess patients' attitudes towards falling and experiences with any subsequent falls. Results Eighty-seven community-dwelling people between the ages of 65 and 90 were recruited, the majority (76%) being women. Seventy-one percent of subjects reported talking to their provider regarding the fall; 37% reported engaging in falls prevention activities. No subjects reported enrolling in a fall prevention program although two reported contacting falls program staff. Fourteen percent of subjects (n=12) reported a recurrent fall and 8% (7) reported returning to the ED after a recurrent fall. Conclusions Findings indicate a low rate of initiating fall prevention behaviors following an ED visit for a fall-related injury among community-dwelling older adults, and highlight the ED visit as an important, but underutilized, opportunity to mobilize health care resources for people at high risk for subsequent falls.